L’assurance-vie face aux nouveaux instruments financiers et à la déréglementation - Sedgwick, Nigel J. (Assurances)

(untitled) (HEC Montréal, 1992)
Deregulation is the outcome of the unification of the industry throughout Europe. Insurance companies have been slow to react to the sweeping change we are witnessing. This is partly owing to the legislation in force in each of the member countries. But, with the emergence of a single European market, the situation is beginning to change. According to the author, Nigel J. Sedgewick, insurers, while remaining competitive, should adopt a more offensive stance by not only gaining more control over general expenses, but also by broadening their range of products to include caps, floors, swaps and others.